2015
DOI: 10.1136/annrheumdis-2015-eular.3402
|View full text |Cite
|
Sign up to set email alerts
|

AB0781 High Sensitivity of the ASAS Classification Criteria in Patients with HLA-B27 Positive Undifferentiated Spondyloarthritis with Onset of Disease After Age 45

Abstract: BackgroundThe spondyloarthritis (SpA) complex also includes forms that do not meet criteria for the definite forms and are called undifferentiated SpA (uSpA). Recently the Assessment in SpondyloArthtritis international Society (ASAS) suggested criteria for axial and peripheral SpA that have substituted the Amor and the European Sondylarthropathy Study Group (ESSG) criteria for all forms of SpA. In the ASAS criteria for axial disease the entry criterion is chronic low back pain in a patient with an age less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The ASAS 2009 criteria for axial SpA and 2011 criteria for peripheral SpA have been validated on patients under 45 years of age, so they are not suitable to use in subjects who develop the disease after this age. Nonetheless, one study suggested that these criteria could be employed when diagnosing patients who develop the disease after 45 years [ 16 , 17 ]. From a therapeutic perspective, the prevalence of comorbidities in older patients, such as heart disease, hypertension, stroke, renal failure, and infections, restricts the use of effective drugs like NSAIDs and biotherapies and requires a vigilant monitoring system and dose reduction [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASAS 2009 criteria for axial SpA and 2011 criteria for peripheral SpA have been validated on patients under 45 years of age, so they are not suitable to use in subjects who develop the disease after this age. Nonetheless, one study suggested that these criteria could be employed when diagnosing patients who develop the disease after 45 years [ 16 , 17 ]. From a therapeutic perspective, the prevalence of comorbidities in older patients, such as heart disease, hypertension, stroke, renal failure, and infections, restricts the use of effective drugs like NSAIDs and biotherapies and requires a vigilant monitoring system and dose reduction [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, one study suggested that these criteria could be employed when diagnosing patients who develop the disease after 45 years [ 16 , 17 ]. From a therapeutic perspective, the prevalence of comorbidities in older patients, such as heart disease, hypertension, stroke, renal failure, and infections, restricts the use of effective drugs like NSAIDs and biotherapies and requires a vigilant monitoring system and dose reduction [ 16 , 18 ]. Furthermore, the therapeutic sensitivity, particularly to NSAIDs, could be lower [ 12 ].…”
Section: Discussionmentioning
confidence: 99%